Cockfighting Gambling Criminal Acts Commitment - Maya Lasena; Fenty U. Puluhulawa; Fence M. Wantu; Ahmad Ahmad (Universitas Negeri Gorontalo, 2022)
This study aims to determinea form of tackling the crime of cockfighting gambling.The method used in this research is empirical or sociological research methodology. This study uses a qualitative approach and sampling using purposive sampling and using descriptive analysis techniques. The results of this study indicate thata form of countermeasure carried out to tackle the crime of cockfighting gambling by means of preventive and repressive measures. In the preventive action stage, basically, stakeholders try to take precautions before the crime occurs. However, the most important role in preventing the occurrence of a crime is the supervision of the local community who then cooperates with law enforcement so that the crime of cockfighting gambling is easily detected.The countermeasures carried out by the authorities should be carried out with good coordination and cooperation, so as to make countermeasures that are right on target.